Cash Transfers and Health : Evidence from Tanzania - Evans, David K.; Holtemeyer, Brian; Kosec, Katrina (Published by Oxford University Press on behalf of the World Bank, 2020)
How do cash transfers conditioned on health clinic visits and school attendance impact health-related outcomes? Examining the 2010 randomized introduction of a program in Tanzania, this paper finds nuanced impacts. An initial surge in clinic visits after 1.5 years—due to more visits by those already complying with program health conditions and by non-compliers—disappeared after 2.5 years, largely due to compliers reducing above-minimal visits. The study finds significant increases in take-up of health insurance and the likelihood of seeking treatment when ill. Health improvements were concentrated among children ages 0–5 years rather than the elderly, and took time to materialize; the study finds no improvements after 1.5 years, but 0.76 fewer sick days per month after 2.5 years, suggesting the importance of looking beyond short-term impacts. Reductions in sick days were largest in villages with more baseline health workers per capita, consistent with improvements being sensitive to capacity constraints. These results are robust to adjustments for multiple hypothesis testing.